The consequences of the 2008 crisis on Britain’s Inflation Targeting Framework - Nathalie Champroux (Revue Française de Civilisation Britannique)
This article demonstrates the extent and limits of the consequences that the 2008 financial crisis and the subsequent economic recession had on Britain’s monetary policy framework. It shows that, beyond the activation of unconventional practices, the crisis caused a reform that was not a complete overhaul of the framework. The bases of the framework dedicated to inflation targeting have been maintained. The value of the reform nonetheless resides in the clarification of the principles of the flexibility of the system and in a move towards a better coordination between monetary and financial policies. The reform is thus embedded in the global progress of monetary theories.